All good people here : a novel - Flowers, Ashley (New York : Bantam, 2022)
"In this propulsive debut novel from the host of the #1 true crime podcast Crime Junkie, a journalist uncovers her hometown's dark secrets when she becomes obsessed with the unsolved murder of her childhood neighbor-and the disappearance of another girl twenty years later. You can't ever know for sure what happens behind closed doors .... Everyone from Wakarusa, Indiana, remembers the infamous case of January Jacobs, who was discovered in a ditch hours after her family awoke to find her gone. Margot Davies was six at the time, the same age as January-and they were next-door neighbors. In the twenty years since, Margot has grown up, moved away, become a big-city journalist. But she's always been haunted by the fear that it could've been her. And the worst part is, January's killer has never been brought to justice. When Margot returns home to help care for her uncle after a diagnosis of early-onset dementia, it all feels like walking into a time capsule. Wakarusa is exactly how she remembered-genial, stifled, secretive. Then news breaks about five-year-old Natalie Clark from the next town over, who's gone missing under eerily similar circumstances. With all the old feelings rushing back, Margot vows to find Natalie and solve January's murder once and for all. But the police, the family, the townspeople-they all seem to be hiding something. And the deeper Margot digs into Natalie's disappearance, the more resistance she encounters, and the colder January's case feels. Could the killer still be out there? Could it be the same person who took Natalie? And what will it cost to finally discover what truly happened that night? Twisty, chilling, and intense, All Good People Here is a searing tale that asks: What are your neighbors really capable of when they think no one is watching?"--
Keywords: Women Journalists; Murder; Missing Persons; Detective and mystery fiction; Thrillers (Fiction); Novels